Details of a Violent Death and Circumstances of Homicide Victims by Firearm in Mexico City (2000-2010) (Andamios, Revista de Investigación Social, 2013)
Firearms are the leading cause of homicide in Mexico City. The aim of this paper is to analyze, from a descriptive-statistical approach, the characteristics of victims and the contexts in which firearms are used in violent death. From an analysis of forensic records, this article argues that the use of firearms is not only part of the increase in criminal activities and organizations, but it also appears to be embedded in a large part of the criminal and violent interactions that occur in the city. The fact that a considerable portion of male victims lost their lives because of a personal dispute solved by a gunshot, or that women lose their lives in a marital dispute settled by a bullet, seems to confirm the weight that the presence of firearms has taken in the everyday life of the city.
Keywords: Homicide; Violence; Firearms; Victims of Homicide